2016
DOI: 10.1002/2211-5463.12030
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of long noncoding RNA SPRY4‐IT1 in melanoma patients

Abstract: Long noncoding RNA SPRY 4‐ IT 1 has been reported to promote melanoma cell growth and invasion, and to block apoptosis. The purpose of this study was to investigate the clinical significance of SPRY 4‐ IT 1 in patients with malignant melanoma. The relative expression levels of SPRY 4‐ IT 1 were measured in plasma samples from 70 patients and 79 healthy controls by quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 36 publications
0
37
0
Order By: Relevance
“…Decreased SPRY4-IT1 expression can inhibit melanoma cell proliferation, motility, and invasion and increase the rates of apoptotic cells. 24 Liu et al 10 investigated the clinical significance of SPRT4-IT1 in melanoma patients and found that SPRY4-IT1 was upregulated in the blood of melanoma patients compared with that in healthy volunteers. High SPRY4-IT1 expression was positively correlated with tumor site and tumor-node-metastasis (TNM) stage and negatively associated with overall survival (OS) rates.…”
Section: Melanomamentioning
confidence: 99%
“…Decreased SPRY4-IT1 expression can inhibit melanoma cell proliferation, motility, and invasion and increase the rates of apoptotic cells. 24 Liu et al 10 investigated the clinical significance of SPRT4-IT1 in melanoma patients and found that SPRY4-IT1 was upregulated in the blood of melanoma patients compared with that in healthy volunteers. High SPRY4-IT1 expression was positively correlated with tumor site and tumor-node-metastasis (TNM) stage and negatively associated with overall survival (OS) rates.…”
Section: Melanomamentioning
confidence: 99%
“…In addition, when these genes were put into enrichment analysis, the results implied that immunization was considered to play a crucial role in the development of CM, as plenty of pathways and functions were associated with immunity. To date, dozens of pathways, such as the integrin/FAK signaling pathway , the KMT2A/hTERT signaling pathway , the PI3K/AKT/mTOR autophagy signaling pathway , and the Wnt signaling pathway , have been determined to somewhat govern the development of CM by disrupting the biological functions of melanocytes. Further statistical analysis of the association between gene expression and the clinical information of CM highlighted several genes, including two lncRNAs, which may influence the outcome of CM patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Liu et al . has demonstrated that lncRNA SPRY4‐IT1 was increased in the plasma of melanoma patients compared to that in healthy controls, and served as an independent predictor for overall survival. In addition, SPRY4‐IT1 was also upregulated in esophageal squamous cell carcinoma , prostate cancer , and gastric cancer .…”
Section: Discussionmentioning
confidence: 99%
“…The SPRY4‐IT1 has demonstrated its overexpression and amplification in multiple cancer types , indicating that it may promote carcinogenesis. Moreover, SPRY4‐IT1 expression has been remarkably correlated with clinical characteristics such as risk, relapse, progression in esophageal squamous cell carcinoma (ESCC) , nonsmall‐cell lung cancer (NSCLC) , clear cell renal cell carcinoma (ccRCC) , gastric cancer , bladder cancer , and melanoma .…”
mentioning
confidence: 99%